2020
DOI: 10.1007/s00405-020-06450-5
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of cochlear implant microphone settings on the binaural hearing of experienced cochlear implant users with single-sided deafness

Abstract: Objective Cochlear implantation has become a well-accepted treatment option for people with single-sided deafness (SSD) and has become a clinical standard in many countries. A cochlear implant (CI) is the only device which restores binaural hearing. The effect of microphone directionality (MD) settings has been investigated in other CI indication groups, but its impact on speech perception in noise has not been established in CI users with SSD. The focus of this investigation was, therefore, to assess binaural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Also, the present report did not control the microphone settings used for the familiar maps, which may influence localization. Better performance has been reported for CI users with the omnidirectional configuration as compared to adaptive [Kurz et al, 2021]. Interestingly, the one listener (Listener 9) who demonstrated poorer performance at the later visit had been listening with an adaptive directionality.…”
Section: Discussionmentioning
confidence: 82%
“…Also, the present report did not control the microphone settings used for the familiar maps, which may influence localization. Better performance has been reported for CI users with the omnidirectional configuration as compared to adaptive [Kurz et al, 2021]. Interestingly, the one listener (Listener 9) who demonstrated poorer performance at the later visit had been listening with an adaptive directionality.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, participants were evaluated with their preferred microphone settings. The directional microphone settings (e.g., adaptive) may have influenced the observed findings, though better localization has been reported with an omnidirectional setting over the adaptive setting 27 . It is also unclear if the improvement seen in variable error is secondary to improved confidence in responses or perhaps increased familiarity with the task; however, task familiarity seems unlikely given that the majority of participants did not present at the 4‐year visit, so they had a 2‐year gap between visits.…”
Section: Discussionmentioning
confidence: 94%
“…The directional microphone settings (e.g., adaptive) may have influenced the observed findings, though better localization has been reported with an omnidirectional setting over the adaptive setting. 27 It is also unclear if the improvement seen in variable error is secondary to improved confidence in responses or perhaps increased familiarity with the task; however, task familiarity seems unlikely given that the majority of participants did not present at the 4-year visit, so they had a 2-year gap between visits. Regarding error measures, corrections for multiple tests were not performed to address the possibility for elevated type 1 error, though trends were supported by individual response plots.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five studies reported speech recognition in noise outcomes. Performance was evaluated with a two-speaker setup in a sound booth in different target-to-masker configurations (colocated versus spatially separated) (20,21,23,24,(26)(27)(28)(29)(30)(31)(32)(33)37,38,(40)(41)(42)44,46,47,49,50,52,55,56). Performance was evaluated with the speech presented from the front (S0) or toward the CI-ear (Sci) and the masking noise either from the front (N0), toward the CI-ear (Nci), or toward the normal hearing ear (Nnh).…”
Section: Speech Recognition In Noisementioning
confidence: 99%